Outcomes and their predictors in schizophrenia in the Northern Finland Birth Cohort 1966 - Juola, P. (Pauliina) (Oulun yliopisto, 2015)
Abstract The aim of this dissertation was to study outcomes in schizophrenia and their predictors in a meta-analysis and in the Northern Finland Birth Cohort 1966 (NFBC 1966). The NFBC 1966 is an unselected, population-based cohort consisting of 12,068 pregnant women and their 12,058 live-born children. This dissertation utilises data that has been collected from medical records, national registers and from two extensive psychiatric studies conducted when the cohort members were 34 and 43 years old, including interview, neurocognitive and brain magnetic resonance imaging data, and questionnaires. Depending on the topic investigated, the sample size ranges between 43 and 103 individuals with schizophrenia. The meta-analysis found that approximately 13.5% of subjects with schizophrenia recovered both clinically and socially, and the recovery rate has not increased in recent decades. Studies from countries with poorer economic indices had higher recovery estimates. In the NFBC 1966, individuals with schizophrenia who were young and single at illness onset, who experienced an insidious onset, and who had more hospital treatment days early on, were at greater risk of a poor outcome in terms of later psychiatric hospitalisations and lack of remission. A novel finding was an association between suicidal ideations at onset and higher number of later psychiatric hospitalisations. Associations were detected between decreased gray matter density in the left frontal and limbic areas and decreased total white matter volume, and concurrent poor outcomes at 34 years. Concerning neurocognitive functioning at 34 years, better long-term verbal memory predicted a better global outcome (symptoms, hospital treatments, social relationships and working combined) and better visual memory predicted a better vocational outcome nine years later. The results of this study show that recovery is possible, but not very common in schizophrenia. Though outcomes are relatively difficult to predict, many clinically relevant predictors were ...